The Effect of Organizational Culture, Organizational Communication Mediated by Work Commitment on Employee Performance PT Tata Bara Utama in Central Kalimantan - Bintang Putra Hidayat; Edison C. Sembiring (Journal of Business and Management Review, 2024)
Research Aims: This study aims to determine the effect of organizational culture, organizational communication mediated by working commitment on employee performance of PT Tata Bara Utama in Central Kalimantan. Design/methodology/approach: This research is a quantitative study by examining the cause-and-effect relationship of the variables of organizational culture, organizational communication mediated by work commitment to the performance of employees a sample of 46 respondents who are still working on the Central Kalimantan project. This research was processed using SmartPLS 3.2. Research Findings: 1) directly organizational culture and organizational communication have a significant and positive effect on employee performance. 2) commitment has no effect on employee performance. 3) Organizational culture has a significant and positive effect on employee performance. 4) organizational communication has no effect on employee performance. 5) indirectly organizational culture and organizational communication have no effect on employee performance mediated by commitment. Theoretical Contribution/Originality: with the research, steps that can be taken by management, namely the need to approach lower-line employees to increase commitment so that it can affect employee performance. Keywords: organizational culture, organizational communication, commitment, employee performance, project.